Personalized Route Recommendation Method for Field Survey Officers using Social Media Information and Administrative Border Maps - Eko Hardiyanto (Proceedings of The International Conference on Data Science and Official Statistics, 2021)
Changes in business processes in pandemic conditions are a must. The field survey were most affected, not only the interview process but also the route selection to survey location. To support the field survey officer, it is necessary to provide alternative route choices to the survey location as fast as possible. This research proposed a methodology that combines three information source, administrative border maps, google maps services, and information from social media that elaborated to provide best recommendation route to the assigned survey location. The combination of three different sources can enhance the current existing route that only relies on google map services. Our mechanism was tested on custom my maps application provided by Google and evaluated using system usability scale. This research aims to give the personalized route to field survey officers based on the assigned survey location and information from social media. The limitation of this research is that the social media channels used are still few, in the future, this research can be leveraged by integrating other platforms owned by the government and other public services to enrich the information.